The existential role of women in The Flies and the dirty hands, by Jean Paul Sartre - NASIF, Majed Jamil; BAQER, Ridha Thamer (Al-Adab Journal, 2021)
The freedom and the existential engagement represent two essential notions in the mind of the writer Jean-Paul Sartre. It has been presented in a good and clear way by his philosophy or, in a clearer way, by his artworks. More specifically, the two plays of this author, The Flies and the dirty hands, are the mirror that reflects these twos existential notions. These two plays are the perfect testimonies for the two important periods in the XXth century: before and after the Second World War. These two periods vary in so far, the human mind, politics and literature as are concerned. This variation has followed the historical and the political changes in the world in general and in France in particular. Even if The Flies and the dirty hands are considered like two different existential dramas, but each one completes the other. The first drama evokes a human mind but, indirectly, another political one, whether the other play evokes the inverse. Oreste and Hugo, the two heroes of our study plays, are the superior heroes who try to save humanity of slavery and submission to injustice. Sartre and his audience place their hopes in these two heroes who search for the freedom through their existential engagement. In the other hand, the female characters have played an affective role in the dramatic action in the two plays. By its freedom and its existential engagement, the female condition, according to Sartre's vision, searches for proving his human existence and revolting against the authority of the family, the society and the humanity.